Development Strategy for Pioneer Tourism Village, Oro-Oro Ombo, East Java - Noviana, Linda; Situmorang, Marningot T Natalis; Farida; Cahyaputri, Bunga; Sukwika, Tatan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The Oro-oro Ombo Pioneer Tourism Village in Batu City, East Java, has significant potential for development as a tourist destination. This study provides clear recommendations for prioritizing alternatives in developing the tourism Village. The Analytic Hierarchy Process (AHP) method is used to identify the factors influencing the development of the tourism village and determine the priority development strategies. This research involves ten respondents representing the Penta helix group: Academics, Business, Community, Government, and Media. Based on the highest and lowest AHP weight values, the research results indicate that local community participation and tourist satisfaction are the key factors. Simultaneously, the results show that the waterfall destination is the main priority alternative (29.9%), followed by the Apple Garden (25.5%), Camping Ground (23.3%), and Flower Garden (21.3%). The study concludes that local community participation is the highest criterion. At the same time, the waterfall destination is the preferred development choice for the Oro-oro Ombo Pioneer Tourism Village in Batu City, East Java. Sustainable development can be achieved by involving the community in decision-making, ensuring environmental conservation, and offering eco-friendly services. Therefore, the policy implication is that local governments should prioritize community engagement, allocate resources for sustainable infrastructure, and support responsible tourism practices.